Importance of infrastructure and system for livestock recording and improvement in developing countries - Westhuizen, J. van der; Scholtz, M.M.; Mamabolo, M.J. (TSAP and ILRI, 2006)
In many developing countries infrastructure and systems for conventional animal improvement are lacking, and the early speculations that marker-assisted selection will provide a quick solution in the absence of such systems have been proven wrong. Systems of livestock recording and improvement have a wider impact on genetic improvement only. Livestock recording is utilised to establish baseline performance, compare production alternatives, improve animal management and genetically improve livestock. The benefits of livestock recording and improvemen to farmers, rural economy, consumers, government and the nation are discussed. The need to secure long term success of animal recording is also highlighted. This includes aspects such as commitment of governments, financial benefit, role of indigenous breeds, socio-economics and infrastructure. This paper attempts to demonstrate how countries without the necessary infrastructure can gain from using existing facilities that exist within a region. An example of such a facility is the Integrated Registration and Genetic Information System (INTERGIS) in South Africa.